Management control practices in uncertain environments : Context of the Covid 19 health crisis. - Rechidi, Nidal; Bennani, Hala; Benazzou, Lotfi (Revue du contrôle, de la comptabilité et de l’audit, 2021)
The Covid-19 pandemic is an exceptional challenge with unique economic and social consequences. It upsets at the same time the forms of work, the structures of the organizations as well as the business management tools. These upheavals have generated an objectively uncertain environment, which poses new challenges to the management control managers, who may not be on the front line to manage the crisis, but are an indispensable pillar since they are led to face the emergency by setting up the appropriate tools for the crisis and by assisting the management in the elaboration of relevant scenarios. This article outlines the results of a qualitative study, which was carried out among a sample of management controllers from different business sectors. The main objective of the study was first to measure the impacts of the crisis on the management control function and then to highlight the changes in management control practices that were necessary to meet the environmental conditions and the organizational choices.